COMPETENCIES OF COGNITIVE PERCEPTION OF PROFESSIONAL KNOWLEDGE OF FUTURE TEACHERS (Scientific journal of the Fergana State University, 2024)
This article reveals the competencies of mastering the professional knowledge of future teachers on the basis of cognitive activity and their role, some issues of the formation of professional knowledge, the importance of cognitive perception, the relevance of the cognitive perception of the professional knowledge of future teachers.